Effect of high dose vitamin D supplementation on indices of sarcopenia and obesity assessed by DXA among older adults: A randomized controlled trial - Jabbour, Jana (2022)
Background Hypovitaminosis D is associated with Sarcopenic Obesity (SO), but evidence from randomized Vitamin D 3 (VD3) trials is scarce. Objective Compare the effect of VD3 supplementation, at two doses, on SO indices at 12 months. Methods Overweight older adults (>65 years) with baseline 25-hydroxyvitamin D (25OHD) of 10–30 ng/mL were recruited in this double-blind, randomized, controlled multicenter trial (clinicaltrial.gov identifier: NCT01315366). All subjects received 1000 mg calcium citrate/day and underwent total body Dual-energy X-ray Absorptiometry for body composition assessment. Low Dose Group (LDG) and High Dose Group (HDG) received 600 IU -Institute of Medicine (IOM) Recommended Dietary Allowance (RDA)- and 3750 IU VD3/day, respectively. Results Mean age was 71 ± 4.6 years, 55% females, BMI: 30.2 ± 4.5 Kg/m2, and 43% had metabolic syndrome. There were no differences in baseline characteristics between groups. At 12 months, 248 participants had body composition data, 122 in LDG and 126 in HDG. Proportions of patients with diminished muscle mass, muscle strength, and visceral adiposity did not differ between the 2 groups at baseline or 12 months. Similarly, no significant differences were noted in the proportion of patients with SO at study entry (1.8% in LDG vs 1.6% HDG; p = 0.99) and at 12 months (3.7% in LDG vs. 0.9% HDG; p = 0.18) across arms. Conclusions Weekly VD3, at the daily equivalent of 3750 IU/day, did not improve indices of sarcopenia nor adiposity compared to the IOM RDA dose in adults.